Construção e validação de checklist para o encaminhamento do paciente hospitalizado à unidade de oxigenoterapia hiperbárica - Araújo, Lianne Clarissa Cavalcanti Eufrázio de (2022)
Seek strategies for the prevention of avoidable damage aimed at qualifying health services. The instruments for early risk verification are part of a low-cost technical tool for error reduction. Considering the importance of monitoring risks and standardizing the care process involving the patient, family members and health professionals who must pay attention to the guidelines regarding preparation for performing Hyperbaric Oxygen Therapy (HBO), this study aimed to build and validate a checklist for the referral of the hospitalized patient to the hyperbaric oxygen therapy unit. This is applied research for the development of a technological product with a quantitative approach, aimed at constructing and validating the checklist's content and appearance. The product was built through the following steps: 1) scoping review on the topic, including the taxonomies of the North American Nursing Diagnosis Association (NANDA) and Nursing Interventions Classification (NIC); 2) construction of the instrument based on the characterization of the checklist items with crossmapping between the result of the scoping review and the titles of the diagnoses in the NANDA I taxonomy, electing the NIC interventions, transforming them into a question format; and 3) content and appearance validation process using the Delphi technique, consisting of a panel of judges (nurses). An active search for judges was carried out through the Lattes platform of the Conselho Nacional de DesenvolvimentoCientífico e Tecnológico (CNPq) and the snowball technique. The study complied with the ethical precepts in research with human beings described in Resolution 466/2012 of the Conselho Nacional de Saúde and is in accordance with the guidelines for research procedures at any stage in a virtual environment, with approval by the University Research Ethics Committee Federal of Rio Grande do Norte, authenticated by opinion No. 4,702,060. In the results, items with the Content Validity Index ≥ 0.90 and the reliability of the checklist by Kappa agreement ≥ 0.80 were considered valid. After the construction and structuring of the checklist, the Delphi step was carried out with the responses of 10 judges, for the validation of content and appearance, containing questionnaires organized through a Likert-type scale (1. totally disagree, 2. partially disagree, 3. partially agree and 4. fully agree). The checklist categorized into 14 items. The 1st round assessed the individual content of the items, the 2nd round assessed the instrument's attributes and the 3rd round the appearance and general assessment. The level of agreement between the judges and the validation of content and appearance reached final values of 1.00. Based on the judges' analysis, it can be concluded that the checklist for referral to the Hyperbaric Oxygen Therapy Units was considered an important support tool and favors the communication process between health teams.